The echo wife - Gailey, Sarah (Tor, 2021)
"'When they said all happy families are alike, I don't think this is what they meant..." Evelyn Caldwell's husband Nathan has been having an affair - with Evelyn Caldwell. Or, to be exact, with a genetically cloned replica. After a morning that begins with a confrontation and ends with Nathan's body bleeding out on the kitchen floor, the two Caldwell wives will have to think fast-before sharing everything includes sharing a jail cell. The Echo Wife is a non-stop thrill ride of lies, betrayal, and identity, perfect for fans of Big Little Lies and Killing Eve"--